Women preaching revolution : calling for connection in a disconnected time - Lawless, Elaine J. (University of Pennsylvania Press, 1996)
Do women preach differently than men? In Women Preaching Revolution Elaine J. Lawless contends that they do. Drawing on her study of more than 150 sermons and extensive interviews with the clergywomen who preached them, Lawless argues that women have changed traditional preaching in ways that reflect their socialization as women and their experiences of being female in America. Many of the women in her study were expected to take courses on the art of preaching as part of their seminary training. Most of them rejected the sermon structure and strategies they were taught in seminary, viewing them as part of a "male" homiletic tradition, and developed styles that celebrate their commitment to connection, relationship, and dialogue.